The School of Salamanca a case of global knowledge production - Duve, Thomas, 1967-; Egío, José Luis; Birr, Christiane (Max Planck studies in global legal history of the Iberian worlds,, 2021)
"This book proposes a different perspective and shows, through a knowledge historical approach and several case studies, that the School of Salamanca has to be considered both an epistemic community and a community of practice that cannot be fixed to any individual place. Instead, the School of Salamanca encompassed a variety of different sites and actors throughout the world and thus represents a case of global knowledge production"--